Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 52311 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Oenocarpus bataua Mart.", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 52311 records from 26 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001878-150811131857512/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences